Proses Pembelajaran Siswa Sekolah Dasar di MI Nurul Hikmah - Siti Nurfaizah; Putri Oktavia (AS-SABIQUN, 2020)
The study was conducted to analyze the relationship between the learning environment and the learning process in an effort to improve student achievement in school, analysis using qualitative methods. Research conducted on madrasa ibtidaiyah teachers NURUL HIKMAH. From this study it can be seen that the learning environment has a positive relationship with student learning achievement, as well as the learning process that has a positive and significant relationship to student learning achievement, this shows that good student achievement can be done in an effort to improve the quality of the learning environment at school and the existence of a quality learning process, thus efforts to improve student achievement can be done by improving and improving the quality of the learning process as well as an increase in the quality of teaching staff in schools so that they are more professional in carrying out their duties and responsibilities as a teacher.